Investigating the effect of full and partial social media abstinence on fear of missing out and well-being outcomes: A daily diary experimental approach - HARTANTO, Andree (Institutional Knowledge at Singapore Management University, 2025)
With social media deeply embedded in our daily lives, there is an ongoing debate about its potential negative impact on well-being outcomes. Several lines of correlational research suggest that social media use is associated with reduced well-being. However, these findings are preliminary, heavily relying on cross-sectional data. To address this limitation, our study implemented an experimental paradigm that manipulated varying degrees of social media abstinence and assessed fear of missing out, as well as multiple well-being outcomes, including anxiety, depressive symptoms, life satisfaction, perceived stress, affective states, loneliness, sleep quality, and cognitive failures. A total of 280 regular social media users were randomly assigned to either a full social media abstinence condition, a partial social media abstinence condition, or a control condition for 7 days. During the experimental period, participants were required to complete a daily survey for 7 days to measure their well-being. Participants in the full abstinence condition reported higher levels of fear of missing out. However, our multilevel modeling revealed no significant impact of either full or partial social media abstinence on the well-being outcomes. More importantly, this null effect was consistent across various personality traits, perceived social supports, cyberbullying experience, and individual differences in social media usage, motives, and network. Our findings challenge the widely held assumption that digital detoxes or social media unplugging interventions are effective strategies for enhancing well-being.